(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
يعدّ هذا العمل متابعة لدراسة أطياف تألق الإصدار الفوتوني التدفقي لإيون البراسيوديميوم Pr3+. قمنا بدراسة تأثير إيون البراسيديميوم بنسية 1% على البلورتين Li2YB5O10, LaF3 فأظهرت البلورة Li2YB5O10 قمماً طيفية عدة أهمها عند الطولين الموجيين 272nm, 300nm، وكان الزمن التألقي الموافق للقمة الأولى هو τ=10.6ns. وأظهرت البلورة LaF3 خطين طيفيين حادين عند الطولين الموجيين 478.6nm, 485.5nm المتعلقين بالانتقالات الطاقية 3P0→3H4. أما زمن التألق لها فكان مساوياً τ=1.8ns. يتبين من هذه الدراسة أن المركبين Li2YB5O10, LaF3 يتمتعان بخصائص تألقية جيدة وهي تعدّ من المركبات الواعدة من أجل تطوير الأجهزة الطبية وخاصة الليزر، وفي المقاييس الإشعاعية وفي مجالات علمية أخرى. This research could be considered as a continuous study of luminescence spectrum of praseodymium cascade photon emission Pr3+ of 1% ions effect on Li2YB5O10 and LaF3 crystals. The Li2YB5O10 crystal shows many spectrum peaks, mainly of 272nm and 300nm wavelengths of luminescence decay τ=10.6 ns. The other crystal LaF3 shows two sharp spectrums of 478.6nm and 485.5nm wavelengths, which are due to the energetic transitions of 3P0→3H4 of luminescence decay τ=1.8 ns. This study proves that these two crystals exhibit good luminescence properties as promising compounds for laser and medical equipments to be used in radiation detectors and other research domains. The measurements were done in Tech-governmental University of Petersburg, Russia, 2008.